2013
DOI: 10.1063/1.4823820
|View full text |Cite
|
Sign up to set email alerts
|

A proposal for an alternative class of spin filter materials: Hybridization-induced high-TC ferromagnetic semiconductors CoVXAl (X = Ti, Zr, Hf)

Abstract: Articles you may be interested inElectron-stimulated desorption from polished and vacuum fired 316LN stainless steel coated with Ti-Zr-Hf-V J. Vac. Sci. Technol. A 32, 061601 (2014); 10.1116/1.4897932Slater-Pauling behavior in LiMgPdSn-type multifunctional quaternary Heusler materials: Half-metallicity, spingapless and magnetic semiconductors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
48
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 34 publications
(39 reference statements)
6
48
1
Order By: Relevance
“…[11][12][13][14][15][16] Although a large number of half-metallic Heusler compounds compounds has been studied, still novel properties are discovered among Heusler alloys, e.g. ferromagnetic or ferrimagnetic semiconducting behavior, [17][18][19][20] paving the way for diverse applications in spintronics/magnetoelectronics.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16] Although a large number of half-metallic Heusler compounds compounds has been studied, still novel properties are discovered among Heusler alloys, e.g. ferromagnetic or ferrimagnetic semiconducting behavior, [17][18][19][20] paving the way for diverse applications in spintronics/magnetoelectronics.…”
Section: Introductionmentioning
confidence: 99%
“…A few halfmetallic FCFiMs have been synthesized, including Mn2RuxGa. 19,20 Recently, a number of quaternary Heusler compounds have been predicted by Galanakis et al to have spin-filter properties and Curie temperatures as high as TC = 2000 K. [21][22][23] Some of these LiMgPdSn-type Y-structure Heusler materials are also fully compensated with zero net moment -thus combining the magnetic advantages of a FCFiM with the spin-filter function, yet having a Curie temperature well above room temperature. One promising SF material is CrVTiAl, which is predicted to crystallize in a Y-type Heusler structure (space group 4 ̅ 3 ), as shown in Fig.…”
mentioning
confidence: 99%
“…In the case of SFMs the most important property is the energy difference in the bottom of the conduction band for the two spin directions, the exchange splitting 2∆E ex , which corresponds to the difference of the barrier that spin up and spin down electrons confront when they tunnel through the SFM [57]. This exchange splitting for the SFMs under study is about 0.1-0.3 eV [26,27]. Thus, the energy quantities characterizing the SGSs and SFMs are relatively small.…”
Section: Motivation and Computational Detailsmentioning
confidence: 99%
“…Firstprinciples electronic band structure calculations have suggested that the ordered quaternary (CoV)YAl and (CrV)YAl Heusler compounds [24,25] -where Y stands for Ti, Zr, or Hf -are SFMs [26,27,28,29]. The former compounds are ferromagnetic semiconductors, while the latter ones are fully-compensated ferrimagnetic semiconductors, as they combine the existence of energy gaps in both spin directions to zero magnetization [26,27]. Both families of Heusler SFMs present high Curie temperatures well above the room temperature and, thus, are of interest for room-temperature spintronic/magnetoelectronic applications contrary to other well known SFMs [30,31,32,33].…”
Section: Introductionmentioning
confidence: 99%